Osteogenic and microstructural characterization in normal versus deformed jaws of rainbow trout (Oncorhynchus mykiss) from freshwater - Godoy, Karina; Sandoval, Cristian; Vásquez, Claudio; Manterola-Barroso, Carlos; Toledo, Barbara; Calfuleo, Joel; Beltrán, Carolina; Bustamante, Marion; Valderrama, Sebastián; Rojas, Mariana; Salazar, Luis A. (Frontiers in Marine Science, 2023)
During the processes of formation and maturation of farmed salmonids, bone deformities could be associated with changes in the mineralization levels of the axial skeleton and the bone-signaling pathways. Therefore, we aimed to evaluate the gene expression during bone formation and regeneration and their relationship with mineralization in rainbow trout with mandibular deformation. We included five normal fish and five specimens with mandibular deformation in smolt rainbow trout weighing 400 g and measuring 25 to 35 cm in length. We assessed 1. serum metabolites, 2. microstructure and mandibular bone mineralization and, 3. gene expression of bone signaling pathways. These analyses were done to determine the main causes and/or mechanisms of deformity. Our results show a marked elevation of bone morphogenetic protein 2 (Bmp2). Also, we found a distinct expression pattern for transcriptional factors, observing diminished RUNX family transcription factor 2 (Runx-2) expression coupled with a simultaneous elevation of osterix (Osx) levels. We also observed decreased osteocalcin and alkaline phosphatase levels related to mineral content loss and an increase in collagen type I as a compensatory structural response. In conclusion, rainbow trout deformation was characterized by demineralization, increased porosity without destruction of the organic matrix, and a moderate decrease in bone mineral content.